DIGITALISASI ARSIP SEBAGAI STRATEGI KEPEMIMPINAN PENDIDIKAN DALAM TRANSFORMASI MANAJEMEN KEARSIPAN MODERN - Bagus Rizky; Maya Salwa Tasliyah; Naila Aisha Putri; Randika Rizal Kurniawan; Siswadi (STKIP Subang, 2026)
The development of information and communication technology has driven digital transformation in various sectors, including archival management in educational institutions. Archive digitization is a crucial strategy for improving the effectiveness, efficiency, and accountability of modern archive management. This study aims to examine archive digitization as an educational leadership strategy for transforming archive management and to formulate appropriate strategies for its implementation. The research method used is library research with a descriptive-analytical approach through the analysis of various relevant literature sources. The results show that archive digitization is an integral part of modern educational transformation, enabling more systematic, rapid, and integrated information management. Furthermore, the successful implementation of archive digitization is strongly influenced by the role of adaptive, innovative, and technology-based educational leadership. A SWOT analysis shows that archive digitization has the strength to increase efficiency and transparency, but also faces weaknesses in the form of limited human resources and infrastructure requirements. On the other hand, there are significant opportunities through technological developments and policy support, as well as threats in the form of data security risks and rapid technological developments. Therefore, an appropriate leadership strategy is needed, including improving human resource competency, technology integration, and strengthening security systems and continuous innovation. Thus, archive digitization is not only a technical change, but also a leadership strategy for realizing modern, effective, and sustainable archives management.